1996
DOI: 10.1006/cbir.1996.0051
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipids and Nuclear Rna

Abstract: It has been demonstrated that in hepatocyte nuclei the chromatin phospholipid fraction is localized near the RNA in decondensed chromatin. The aim of the present study was to see if there is any linkage between phospholipids and other nuclear components. Isolated hepatocyte nuclei and nuclear membranes were treated with deoxyribonuclease and ribonuclease. No loss of phospholipids was observed after DNA digestion, whereas 48% was lost following enzymatic RNA removal. This loss of phospholipids, localized either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 23 publications
3
24
0
Order By: Relevance
“…The simultaneous treatment with phospholipase A2 and RNA colloidal gold using particles of different sizes revealed that nuclear PLs and RNA have a similar location inside the nucleus. 23 The relation between RNA and PLs was confirmed by the fact that digestion of isolated hepatocyte nuclei with DNase did not change the PL content whereas a decrease of 40% was observed after DNase and RNase treatment 24 ( Figure 3). The loss was not equal for each PL.…”
Section: Sphingomyelin Presence and Localizationmentioning
confidence: 78%
See 1 more Smart Citation
“…The simultaneous treatment with phospholipase A2 and RNA colloidal gold using particles of different sizes revealed that nuclear PLs and RNA have a similar location inside the nucleus. 23 The relation between RNA and PLs was confirmed by the fact that digestion of isolated hepatocyte nuclei with DNase did not change the PL content whereas a decrease of 40% was observed after DNase and RNase treatment 24 ( Figure 3). The loss was not equal for each PL.…”
Section: Sphingomyelin Presence and Localizationmentioning
confidence: 78%
“…25 The result expressed as mg mg À1 of protein confirmed the strong decrease in SM after RNAse digestion. 24 When the hepatocyte nuclei were treated with Triton-X-100 to remove the external envelope and digested with DNAse and RNAse the remaining material was mostly constituted by protein, but a small amount of RNAse-resistant RNA remained together with PLs. Chromatographic analysis showed that only two PLs, SM and phosphatidylcholine (PC) were present 26 ( Figure 4).…”
Section: Sphingomyelin Presence and Localizationmentioning
confidence: 99%
“…Lipids are present in many cellular structures containing DNA and proteins, for instance, in nuclear matrix [12], nucleoid [13] and chromatin [14][15][16][17][18][19][20]. Literature provides more data on the presence of lipids in chromatin as compared to those in nuclear matrix and nucleoid.…”
Section: Lipids Of Chromatinmentioning
confidence: 99%
“…The relation of these lipids to transcription and replication processes could be interpreted by their close associations with DMC (nuclear pores and transcription factories). It has been demonstrated that in hepatocyte nuclei the chromatin phospholipid fraction is localized near the RNA in decondensed chromatin [18]. The necessity of developing new method of isolation of lipids tightly bound to chromatin (DMC) without using organic solvent and detergent is still relevant for these authors.…”
Section: Lipids Of Chromatinmentioning
confidence: 99%
“…The occurrence of phospholipids in nuclei has been documented by biochemical and ultracytochemical procedures [2,3]. The total phospholipid content of nuclei is reported as 3% by weight compared with 75% for protein and 22% for DNA.…”
Section: Introductionmentioning
confidence: 99%